Assessment of Health-Promoting Lifestyle in Female Students - Nader Sharifi; Farangis Sharifi; Malikeh Amel Barez; Habibollah Esmaily (Mashhad University of Medical Sciences, 2020)
Background & aim: Lifestyle is a way of living, which has effects on people's health. Health-promoting lifestyle (HPL) is a component of health promotion and includes six dimensions. This study aimed to assess the different dimensions of health-promoting lifestyle in female students. Methods: This cross-sectional study was carried out on 133 female students of Islamic Azad University, Iran. Who were selected using a multi-stage random sampling. Data was collected through a demographic as well as Walker's lifestyle questionnaire regarding the six dimensions of HPL. The collected data were analyzed in SPSS software (version 24) using descriptive statistics, independent t-test, and Friedman nonparametric test. Results: The mean lifestyle score of students was 50±3.7 (%), which was considered as a moderate level of lifestyle. Mean score of nutrition (54.9±8.8%) and exercise (53.6±8.6%) was at the highest level. The score of other dimensions included self-actualization (51.5±7.5%), health responsibility (46.6±6%), interpersonal support (46.9±5%), and stress management (43.4±6.9%) was on a moderate level. In this study, the total score of lifestyle correlated significantly with the housing status of students, smoking, and coffee consumption (P<0.05). Conclusion: The total score of lifestyle was on a moderate level. The score of stress management, interpersonal support, and health responsibility dimensions was on the lowest level.  Accordingly, it is of utmost importance to provide the students with the education and social support programs, thereby improving their lifestyle with an emphasis on these dimensions.